2018
DOI: 10.1002/pbc.27422
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in the proportion of “cure” in children, adolescents, and young adults diagnosed with chronic myeloid leukemia in England: A population‐based study

Abstract: The striking improvement of the "cure" fraction in young patients with CML since the early 1980s is concomitant with improvement of treatment, especially the allogeneic hematopoietic stem-cell transplant and, later, the introduction of TKI. The trends over the last years (2000-2005) remain, however, uncertain and would benefit from further studies with more recent data and updated follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The introduction of (life-long) tyrosine kinase inhibitor treatment, which specifically targets BCR-ABL, often found in CML patients, likely also resulted in the high survival gains and favourable outcomes that were observed for all CML patients at AYA age in this study [9,13,63].…”
Section: Chronic Myeloid Leukaemiamentioning
confidence: 87%
“…The introduction of (life-long) tyrosine kinase inhibitor treatment, which specifically targets BCR-ABL, often found in CML patients, likely also resulted in the high survival gains and favourable outcomes that were observed for all CML patients at AYA age in this study [9,13,63].…”
Section: Chronic Myeloid Leukaemiamentioning
confidence: 87%
“…In the first two decades of life, CML is exceptionally rare in infancy, reportedly 0.7/million/year at age between 1 and 14 years, and rising to 1.2/million/year in adolescents. 4,5 A few studies have focused on clinical and biological data of CML at pediatric and adolescent ages. 6,7 In the largest trials so far on pediatric CML (CML-paed-I, CML-paed-II), only two and three patients, respectively, were younger than 3 years at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…As the incidence of CML increases with age, some of these variations are due to significant differences in the age distributions of the investigated populations (eg, Western vs non‐Western countries, age range of pediatric cohorts 0‐14 years, 0‐16 years, or 0‐18 years). In the first two decades of life, CML is exceptionally rare in infancy, reportedly 0.7/million/year at age between 1 and 14 years, and rising to 1.2/million/year in adolescents 4,5 . A few studies have focused on clinical and biological data of CML at pediatric and adolescent ages 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Were the tests ordered as part of routine clinical care? The study design needs clarification.Instead of reporting 100% sensitivity "among the patients with HM and confirmed infections", I would prefer to (also) see the "overall agreement" of 70% with standard micro methods.There is limited data on Karius performance for invasive mold infections, and the authors should acknowledge that, referring to additional studies, specifically DMID 2018;92:210 1 (7 of 9 pts correctly identified), Pediatr Blood Cancer 2018;66:e27734 2 (4 of 6 pts correctly identified).…”
mentioning
confidence: 99%
“…There is limited data on Karius performance for invasive mold infections, and the authors should acknowledge that, referring to additional studies, specifically DMID 2018;92:210 1 (7 of 9 pts correctly identified), Pediatr Blood Cancer 2018;66:e27734 2 (4 of 6 pts correctly identified).…”
mentioning
confidence: 99%